Bodies in Flux : Embodiments at the End of Anthropocentrism - Muzaffar, Hanan (2019)
This volume discusses fluidity of the post-human bodies on various cultural and social examples - from the cyber relations to others and to self, through fragmented, prosetheticised, monstrous or augmented body, to the dis/utopian fantasies.